Evaluation of Crofton, Horne, Miller Scoring as Diagnostic Tool for Tuberculosis in Children - Giri, Arun; Sah, Vijay Kumar; Yadav, Sunil Kumar; Niraula, Niraj (Journal of Nobel Medical College, 2019)
Background: Tuberculosis which is caused by Mycobacterium tuberculosis a chronic infectious disease is considered the second most common infectious cause of mortality and morbidity in children around the world. This study was carried out to test the validity of Crofton, Horne and Miller scoring system for the diagnosis of children suffering from tuberculosis. Materials and Methods: It was done in an inpatient ward of a pediatric tertiary referral centre, from Feb 2018 to Jan 2019as a prospective case control study, including 92 children aged 2 years to 12 years admitted with clinical differential diagnosis of tuberculosis. Among them 46 children meeting the case definition were taken as cases and 46 were age, sex and disease presentation matched controls. Results: Sensitivity of the score was low (50%) but the specificity was high (95%) with 92% positive predictive value and a negative predictive value of 65.67%. Contact with an adult suffering from tuberculosis, positive Mantoux test (>10mm in duration) were found to be the most important indicators of TB in children. Males were found to be affected twice as much as the females. Conclusion: From the findings of the study, it can be concluded that the Crofton, Horne, Miller score chart is a simple and cost-effective tool, which can be applied to improve the diagnosis of TB in children due to financial constraints faced by patients in resource limited countries like Nepal.